Comparative study of rules employed for calculation of pediatric drug dosage - Elias, Gracieli Prado [UNESP]; Antoniali, Cristina [UNESP]; Mariano, Ronaldo Célio (Faculdade De Odontologia De Bauru - USP, 2005)
The present study was conducted to evaluate the utilization of Clark's, Salisbury and Penna's rules and the Body Surface Area (BSA) formula for calculation of pediatric drug dosage, as well as their reliability and viability in the clinical use. These rules are frequently cited in the literature, but much controversy still exists with regards to their use. The pediatric drug dosage was calculated by utilization of the aforementioned rules and using the drugs Paracetamol, Dipyrone, Diclofenac Potassium, Nimesulide, Amoxicillin and Erythromycin, widely employed in Pediatric Dentistry. Weight and body surface areas were considered of children with ages between 1 and 12 years old as well as the dosage for the adult. The pediatric dosages achieved were compared to the predetermined dosages in mg kg-1 herein-named standard dosages. The results were submitted to the parametric test ANOVA and to the Tukey test (p<0,05). The antibiotics and Diclofenac provides acceptable utilization of the rules in pediatric dentistry, however for the Dipyrone, the dosages obtained by the rules suggest their clinical ineffectiveness. For the Paracetamol, the Penna's rule and the BSA formula should not be clinically employed, especially for children between 1 and 5 years old, once such dosages were much close to the hepatotoxic dosage of the drug. It can be concluded that the use of the rules for safe calculation of the pediatric drug dosage is possible and it depends on the used drug and age group.

O presente estudo foi realizado com a finalidade de avaliar as fórmulas de Clark, Salisbury, Área da Superfície Corpórea (ASC) e Penna, quanto a sua confiabilidade e viabilidade de uso clínico para o cálculo de doses medicamentosas infantis, uma vez que tais fórmulas são freqüentemente citadas na literatura, mas muita controvérsia ainda existe com relação ao seu uso. As doses infantis foram calculadas utilizando as fórmulas descritas e os medicamentos Paracetamol, Dipirona, Diclofenaco de Potássio, Nimesulida, Amoxicilina e Eritromicina, largamente usados na clínica odontopediátrica. Foram considerados parâmetros como o peso e área da superfície corpórea de crianças com idades entre 1 e 12 anos e a dose para o adulto. As doses obtidas foram comparadas às doses em mg/kg consideradas como padrão de referência para os medicamentos. Os resultados foram submetidos ao teste paramétrico ANOVA e de Tukey (P<0,05). Os antibióticos e o Diclofenaco propiciam utilização aceitável das fórmulas na Odontopediatria, porém para a Dipirona, as doses obtidas pelas fórmulas sugerem ineficácia clínica. Para o Paracetamol, o uso clínico das fórmulas de Penna e da ASC para crianças entre 1 a 5 anos é contra-indicado, uma vez que as doses obtidas com tais fórmulas aproximaram-se muito das doses hepatotóxicas do medicamento. Pode-se concluir que o uso das fórmulas para o cálculo seguro de doses infantis é viável, dependendo do medicamento utilizado e da faixa etária.
Estudo comparativo de fórmulas empregadas no cálculo de doses medicamentosas infantis
Keywords: Pediatric dentistry; Oral administration; posology; Odontopediatria; Administração oral de medicamentos; posologia